2022
DOI: 10.13189/saj.2022.100408
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Leg Muscle Explosive Power, Agility, and Self-confidence on Sickle Kick Performance

Abstract: There are many factors affecting Pencak Silat performance, including physical, mental and kicking technique. Based on the preliminary study, it was found that the sickle kick ability of PSN Badai Kuamang Kuning college athletes was low. Thus, the purpose of this study was to know the effect of leg muscle explosive power, agility and confidence on sickle kick. This research used the quantitative approach (path analysis). There were 30 male athletes aged 15-18 years taken as samples through total sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…This agrees with [15,16] indicated that there is a correlation between physical abilities, power and agility cannot be improved separately, but should improve by involving different physical abilities during the training sessions [17], such as MDT training protocol.…”
Section: Discussionsupporting
confidence: 85%
“…This agrees with [15,16] indicated that there is a correlation between physical abilities, power and agility cannot be improved separately, but should improve by involving different physical abilities during the training sessions [17], such as MDT training protocol.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, in pencak silat, traditional weapons such as swords, machetes, sticks, spears, celurit, knives, tridents, kerambit (a type of knife), keris, and others are taught. Pencak Silat in the psychomotor domain is inseparable from biomechanics, under-standing the factors that govern human movement is very important for technique (Ihsan et al, 2022;Kusuma & Novita, 2023;Muzakki et al, 2023). Harnessing biomechanics for training enables intelligent training planning so you can get the most out of it in the shortest time and in the safest way.…”
Section: Discussionmentioning
confidence: 99%
“…There is much previous research concerning Pencak silat, such as training methods to improve the capacity of cardiovascular endurance of the Pencak silat athlete [9], to improve core strength muscle, and dynamic balance [10]. Besides that, there is also research related to the leg muscle power effect on cycle kick performance [11], the leg muscle power effect on straight kick skill [12], and the training method that has a significant effect on Pencak silat kicking skill [13].…”
Section: Introductionmentioning
confidence: 99%